DEVELOPMENT OF THE FINANCIAL MECHANISM FOR PROVIDING THE STATE GUARANTEES OF POPULATION MEDICAL SERVICE: FOREIGN PRACTICE - KARPENKO, LIDIIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Scientific research consists of substantiation and development of conceptual foundations and recommendations for the development of a financial mechanism for providing state guarantees of medical care to the population based on foreign practice. The paper substantiates the relevance of building an effective financial mechanism for ensuring state guarantees of medical care for the population for the Ukrainian medical sphere is: the need to reform the healthcare system in Ukraine; changing the paradigm of financing the medical industry; financing of the medical industry is experiencing critical problems; catastrophic situation in ensuring the provision of specialized and highly specialized inpatient care; imperfection of mechanisms for ensuring financing of the health care system of Ukraine.In this work, the author examines in detail the features of the three main models of healthcare at the global level, classifies the healthcare systems of leading countries according to three main models, systematizes in tabular form the practice of six countries - Israel, Sweden, France, the USA, Great Britain Germany, in which these models received the most bright embodiment.The aim of the work consist of  studding the general principles of financing models and organization of the health care system in the coordinates of globalization changes and European integration; analysis and characterization of the financial mechanism that provides state guarantees in the field of medical care Applied aspects are based on the systematization of the instrumental base for modelling the financial mechanism for providing state guarantees of medical care to the population, taking into account foreign experience.In the work, the author analyzed the calculations of the ratio of costs and indicators of the effectiveness of the health care system in 2020, the analytical dependence of average life expectancy on per capita expenditures in the health sector, % of GDP.The analysis carried out on the selected research issues provides a conceptual basis for the formation of an effective financial mechanism for budget policy in Ukraine to ensure state guarantees of medical care for the population; forms a platform for the development of macroeconomic stabilization policy. The prospects for further research are the improvement of the issues of the mechanism for the effective functioning of the public sector and the implementation of integrated management analysis.
Keywords: financial mechanism; state guarantees; healthcare system; consumer health index; healthcare models; financial support; insurance model